En analys av incidentrapporter för DP-fartyg med avseende på positionsreferenssystem och deras felkällor - Lindskog, Jonas; Sjömar, Fredrik (My University, 2015)
DP (Dynamic Positioning) is a rapidly developing computer-controlled navigation system used in the shipping industry, particularly in the offshore industry, that depends greatly on accuracy and redundance. DP allows a ship to either hold its position with active trust or follow a predetermined path with high precision. PRS (Position Reference System), which is one of the most important components of a DP system, will be the focus of our research; in particular, the satellite based PRS commonly known as GNSS. Our paper consists of a background study of the PRS and their function in the DP system, as well as a quantitative analysis of reported incidents. We have found a link between GNSS-related incidents and the solar cycle (solar activity). This relationship could be an indication of how GNSS are affected by ionospheric activity, however, since the statistical data used in this study has been limited, the results should be interpreted accordingly.
Keywords: Annan teknik; Transport; Other Engineering and Technologies; Transport